2000
DOI: 10.1023/a:1008180020974
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: SummaryThe EVA structural descriptor, based upon calculated fundamental molecular vibrational frequencies, has proved to be an effective descriptor for both QSAR and database similarity calculations. The descriptor is sensitive to 3D structure but has an advantage over fieldbased 3D-QSAR methods inasmuch as structural superposition is not required. The original technique involves a standardisation method wherein uniform Gaussians of fixed standard deviation (σ) are used to smear out frequencies projected onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Also many different quantum chemistry-based descriptors such as TQSI, MQSM, and QS-SM 9 have been developed, most of which are based on the molecular orbital (MO) approach . Spectral information can also be used as a basis for QSAR analysis, as is demonstrated by the success of CoSA, EVA, and EEVA approaches, which utilize IR, RAMAN, NMR, and MO energy spectra for QSAR. Many so-called E-state techniques , utilizing parameters derived from electrotopological structure of molecules have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Also many different quantum chemistry-based descriptors such as TQSI, MQSM, and QS-SM 9 have been developed, most of which are based on the molecular orbital (MO) approach . Spectral information can also be used as a basis for QSAR analysis, as is demonstrated by the success of CoSA, EVA, and EEVA approaches, which utilize IR, RAMAN, NMR, and MO energy spectra for QSAR. Many so-called E-state techniques , utilizing parameters derived from electrotopological structure of molecules have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…That is the price that one must pay by requiring the detailed characterization of a three-dimensional molecular property field, whether it is steric, electrostatic, or hydrophobic. There have, however, been a number of characterizations dependent upon three-dimensional structure that capture molecular features in ways not requiring an alignment or superposition step for the assignment of molecular similarity. The alignment-free procedures also generate a relatively small set of three-dimensional descriptors, thus enabling greater ease of statistical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic QSAR Methods. A set of QSAR methods have recently been put forward in which vibration frequencies (EVA, eigenvalue, i.e., vibrational normal mode in this context), MO energies (EEVA, electronic eigenvalue), and NMR chemical shifts (CoSA, comparative spectra analysis and its modifications ) are used to derive QSAR descriptors. It has been shown that spectroscopic methods can provide robust, predictive QSAR models for a large number of biological data sets.…”
Section: Introductionmentioning
confidence: 99%